HLA antigens and acetylcholine receptor antibody in the subclassification of myasthenia gravis in Hong Kong Chinese. Issue 3 (March 1986) - Hawkins, B R; Ip, M S; Lam, K S; Ma, J T; Wy, C L; Yeung, R T; Dawkins, R L
Abstract : Thirty seven Chinese adults and 23 children in Hong Kong with myasthenia gravis were tested for HLA-A and -B antigens and acetylcholine receptor (AChR) antibody. HLA BW46 had a significantly increased prevalence in patients with juvenile onset ocular myasthenia gravis. Only one third of the juvenile ocular patients had AChR antibodies and the titres were generally low. In the adult patients taken as a whole there was a non-significant increase in the prevalence of HLA B5 and HLA B15. HLA BW46 was more prevalent in adult patients without AChR antibody and less prevalent in patients with AChR antibody but the findings were not statistically significant. It is suggested that ocular myasthenia gravis is determined by a pathological mechanism for which susceptibility is determined by HLA BW46. There was a strong correlation between ocular myasthenia gravis and Graves' disease in the adult patients. The possibility that ocular myasthenia gravis is accentuated by a BW46-associated predisposition to ocular Graves' disease is considered.